COVID-19 Vaccination and Ukrainian Refugees in Poland during Russian–Ukrainian War—Narrative Review - Wojciech Malchrzak; Mateusz Babicki; Dagmara Pokorna-Kałwak; Zbigniew Doniec; Agnieszka Mastalerz-Migas (Vaccines, 2022)
The outbreak of the Russian–Ukrainian war contributed to the largest migration movement in the 21st century. As a result, over 3 million refugees, mainly women, children and the elderly, arrived in Poland in a short space of time. Despite the ongoing war, it is important to remember that the COVID-19 pandemic is still present in the world, and before the outbreak of the war, Ukraine was struggling with its fifth wave. Furthermore, Ukraine has one of the lowest vaccination rates in Europe, not exceeding 40%. It is, therefore, reasonable to suspect that the vast majority of migrants have not been vaccinated. This situation may pose a significant epidemiological risk. Therefore, it is necessary to implement appropriate steps to determine the vaccination status of refugees and to supplement the vaccination with both the core and booster doses. In response to these needs, the government of Poland, like many other countries, has made it possible to provide free COVID-19 vaccination to persons fleeing war. In the face of massive migration, the overriding priority should be to ensure adequate medical care for refugees, including free COVID-19 vaccinations. However, it seems that the lack of willingness to vaccinate among Ukrainians is also replicated on migration. It seems reasonable that appropriate steps should be taken to increase awareness and confidence in vaccination, which may ultimately translate into increased vaccination uptake. Analyzing previous experiences, it is advisable to consider that the first step should be to promote vaccination and remind refugees of the possibility of free COVID-19 vaccination. Additionally, refugees should be encouraged to be vaccinated during every contact with health care workers.